20 February, 05:54
3) Find f (-1) when f (x) = x2+3x + 4.
C) - 6
20 February, 07:17
f (x) = x²+3x + 4.
→ f (-1) = (-1) ²+3 (-1) + 4
= 1 - 3 + 4
= 5 - 3
Know the Answer?
New Questions in Mathematics
The Phoenicians manufactured items out of • A) glass and metal OB) gigantic slabs of stone 0 C) animal hair
Which is an example of non-specific immunity?* O antibodies are produced by B cells O cytotoxic T cells kill infected cells memory B cells are produced O inflammation increases blood flow to the affected area
You see lightning before you hear thunder because A) light waves can travel through a vacuum. B) sound waves cannot travel through the air. C) light waves travel faster than sound waves. D) sound waves travel faster than light waves i think its c .
What is the answer to - 24-1/8p=3/8p?
Eduardo bought a refrigerator with a sticker price of $2400. If he paid $35 a week for two years, what was the approximate markup rate on the refrigerator? A. 65.9% B. 51.7% C. 34.1% D. 75.8%
» 3) Find f (-1) when f (x) = x2+3x + 4. A) B) 2 C) - 6